Adverse events reported by anxious school refusing adolescents receiving cognitive behavioral therapy with and without fluoxetine. (October 2019) - Melvin, Glenn A; Finnin, Linda; Taffe, John; Dudley, Amanda L; Klimkeit, Ester I; Gordon, Michael S; Tonge, Bruce
Background: Investigating adverse events associated with antidepressant treatments in adolescents is important given the concerns about increased risk of suicidal ideation and behavior in this age group. The aim of this study is to investigate adverse and serious adverse events associated with the treatment of anxiety (cognitive behavioral therapy (CBT)-only, CBT-plus-placebo, and CBT-plus-fluoxetine) in anxious school-refusing adolescents. Methods: A side-effect symptom checklist was completed by participants prior to commencing treatment and during treatment (weekly/fortnightly). Results: CBT-plus-fluoxetine was well tolerated and not associated with higher levels of adverse events than the other treatments. Adverse events in all groups decreased over time, and the only adverse event distinct to fluoxetine was nausea. Baseline anxiety predicted higher levels of adverse events. There was one suicide attempt in the CBT-plus-placebo group but no statistically significant difference in suicide attempts between groups. Participants with a comorbid depressive disorder were more likely to report self-injury ideation but not suicidal ideation compared with those who did not have comorbid depressive disorder. Frequency of suicidal ideation and non-suicidal self-injury was significantly lower in the CBT-plus-fluoxetine group compared with the CBT-only group. Frequency of self-injury ideation was significantly lower in the CBT-plus-fluoxetine group compared with both other groups. Conclusions: Overall, the treatments were well tolerated and fluoxetine plus CBT appeared to be protective against suicidal ideation, non-suicidal self-injury, and self-injury ideation in this sample.